Disadvantage and discrimination in self-employment: Caste gaps in earnings in Indian small businesses - Ashwini Deshpande; Smriti Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Using the 2004-05 India Human Development Survey data, we estimate and decompose the earnings of household businesses owned by historically marginalized social groups known as Scheduled Castes and Tribes (SCSTs), and non-SCSTs across the earnings distribution. We find clear differences in characteristics between the two types of businesses with the former faring significantly worse. The mean decomposition reveals that as much as 55 per cent of the caste earnings gap could be attributed to the unexplained component. Quantile regressions suggest that gaps are higher at lower deciles, providing some evidence of a sticky floor. Finally, quantile decompositions reveal that the unexplained component is greater at the lower and middle deciles than higher, suggesting that SCST-owned businesses at the lower and middle end of the conditional earnings distribution face greater discrimination.
Keywords: J31; J71; C21; O15; O17; 330; caste; discrimination; household business; earning gaps; quantile decomposition; India